2018
DOI: 10.1093/femsle/fny088
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance phenotypes and virulence-associated genes in Escherichia coli isolated from animals and animal food products in Tunisia

Abstract: Livestock and food products of animal origin constitute important reservoirs of intestinal and extraintestinal pathogenic Escherichia coli including antibiotic-resistant E. coli isolates. To assess potential risks to public health related to E. coli strains of animal origin in Tunisia, 65 E. coli isolates recovered from healthy animals and food products of animal origin were studied. Antimicrobial susceptibility was determined according to CLSI guidelines and genes encoding antibiotic resistance as well as vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 49 publications
2
12
1
Order By: Relevance
“…The E. coli resistance to trimethoprim-sulfamethoxazole in this study were 21.1%, that was similar to the research conducted by Badi et al (2018) which showed that E. coli resistance to trimethoprim-sulfamethoxazole were 36.9%. The second-highest resistance in this study occurred to ampicillin (26.3%), contrary to the study conducted by Messele et al (2017) that found high occurance (71.4%) of the E. coli resistance to oxytetracycline (5.3%) and ciprofloxacin (21.1%) in this study was lower than the study conducted by Rahman et al (2017) which reported the resistance in oxytetracycline (71.43%) but not resistant to ciprofloxacin (100% sensitive).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The E. coli resistance to trimethoprim-sulfamethoxazole in this study were 21.1%, that was similar to the research conducted by Badi et al (2018) which showed that E. coli resistance to trimethoprim-sulfamethoxazole were 36.9%. The second-highest resistance in this study occurred to ampicillin (26.3%), contrary to the study conducted by Messele et al (2017) that found high occurance (71.4%) of the E. coli resistance to oxytetracycline (5.3%) and ciprofloxacin (21.1%) in this study was lower than the study conducted by Rahman et al (2017) which reported the resistance in oxytetracycline (71.43%) but not resistant to ciprofloxacin (100% sensitive).…”
Section: Discussionsupporting
confidence: 89%
“…The resistance to cefotaxime in this study (21.1%) was higher compared to the study conducted by Badi et al (2018) which found a 7.7% of resistance in cefotaxime. The resistance in cefotaxime was considered as an early warning because cefotaxime was one of the third generations of cephalosporin that was known as drugs of choice in bacteremia caused by Gram-negative bacteria in humans (Park, 2014).…”
Section: Discussioncontrasting
confidence: 79%
“…The EPEC-a strains have been detected in birds reared in the conventional system and its products (Dutta et al 2011, Alonso et al 2012, Samanta et al 2015, Doregiraee et al 2016, Badi et al 2018, as occurred in the present study.…”
Section: Epec and Stec Characterizationsupporting
confidence: 73%
“…The Enteropathogenic Escherichia coli (EPEC) and Shigatoxigenic E. coli (STEC) strains are pathogens of public health importance due to their ability to cause enteric diseases in humans (Ifeanyi et al 2016, Fierz et al 2017, Torres 2017) these pathogens are isolated from poultry and poultry products (Dutta et al 2011, Alonso et al 2012, Samanta et al 2015, Doregiraee et al 2016, Badi et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Foods of animal origin are considered serious sources of food-borne diseases worldwide. Moreover, the situation worsens in developing countries due to difficulties in achieving optimum hygienic food handling practices (Schlundt et al, 2004;Newell et al, 2010;Badi et al, 2018). Foodborne pathogens cause high economic losses in developing countries due to medical care and social costs (Fratmico et al, 2005).…”
Section: Introductionmentioning
confidence: 99%